(untitled) (Linguostylistic Studies, 2023)
The article considers the processes of Anglo-barbarization as unmotivated borrowings of anglicisms in the Ukrainian language. The subject of the study is the issue of creating specific Ukrainian equivalents to the borrowed anglicisms. Firstly, the Ukrainian language’s capacity to create new words, taking into account motives for the nomination and socio-cultural circumstances; and, secondly, the search for a balance model of foreign and specific words with a linguistic-national priority; thirdly, an analysis of the socio-psychological motives of Anglo-barbarization. The model for etymological and lexical-semantic analysis is the Anglicism стейкголдер [stakeholder], its Ukrainian equivalents, and the author’s new formation користач(і). The issue of the new formations as substitutes for common anglicisms is one of the most relevant not only in the lexical-semantic structure of the language. It also signals the ideological self-sufficiency or dependence of the nation, in particular, its leadership. The most numerous group of lexical-semantic assimilation of anglicisms is Barbarization, considered as an unmotivated borrowing with an existing unattractive equivalent in translation dictionaries (64.6%), which indicates a very low level of use of the recipient’s language resources and neglect of the balance model of foreign and specific words. The proposed author’s new word formations, which make up 10%, testify to the inexhaustible possibilities of the Ukrainian language in the field of word formation, the expansion of the lexical-semantic field of lexemes, and specific socio-cultural motives of the nomination. The study focuses on the etymological and lexical-semantic analysis of the lexeme стейкголдер [stakeholder] and one of its Ukrainian equivalents, користач(і). At the same time, the problem of introducing specific new formations lies in the socio-psychological plane of national complexes and depends on their onward orientation towards foreign linguistic and political influences.